2009
DOI: 10.1021/ol900098q
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Transfer Catalysis with 1,2,4-Triazole Anion

Abstract: Abstract1,2,4-Triazole anion has been identified as an active acyl transfer catalyst suitable for the aminolysis and transesterification of esters.Neutral nucleophiles (Figure 1), such as 4-dialkylaminopyridines (1), 1 N-alkylimidazoles (2), 2 phosphines (3), 3 imidazolylidene carbenes (4), 4 1,2-diamines (5), 5 and the recently introduced bicyclic amidines (6) and isothioureas (7), 6 have proved to be effective acyl transfer catalysts. As such, they have found a variety of applications in organic synthesis. 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 33 publications
0
84
1
Order By: Relevance
“…(1) Reaction of benzylamine with isopropenyl acetate (10) in acetonitrile proceeds to N-benzylacetamide (12) in approximately 50% yield in six hours (Figures S9-S11) [26,27]. In the presence of CO2 and 1.1 equivalents of DBU, however, no detectable product was observed during the same time period as analyzed by 13 C NMR.…”
Section: In Situ Protection Of Amines With Co2mentioning
confidence: 99%
“…(1) Reaction of benzylamine with isopropenyl acetate (10) in acetonitrile proceeds to N-benzylacetamide (12) in approximately 50% yield in six hours (Figures S9-S11) [26,27]. In the presence of CO2 and 1.1 equivalents of DBU, however, no detectable product was observed during the same time period as analyzed by 13 C NMR.…”
Section: In Situ Protection Of Amines With Co2mentioning
confidence: 99%
“…These data indicated that the phenyl ester reacts first (in a rate-limiting step, see Scheme 3) with imidazole to form a highly reactive intermediate (presumably acyl imidazole). Then the intermediate reacts rapidly with Cys through thiol capture [9] or it is destroyed by H 2 O when Cys is absent. To apply the phenyl ester ligation to protein chemical synthesis, we developed a solid-phase method to prepare peptide phenyl esters (Scheme 4).…”
mentioning
confidence: 99%
“…The use of sodium methoxide in toluene for amidation of unactivated esters [35] failed. However, aminolysis of acetonide-ester 3 was successfully performed with 1,2,4-triazole anion as catalyst [36], but in a moderate yield, to provide N-propargylamide derivative of acetonide 4. The acetal deprotection of 4 was carried out with Dowex ® 50 resin in methanol to give the key intermediate 5 in good yield.…”
Section: Synthesis Of New Gnlsmentioning
confidence: 99%